2013
DOI: 10.1080/09205063.2013.804758
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of antibacterial PVA and PEO nanofibers containing Lawsonia Inermis (henna) leaf extracts

Abstract: Concerns about health issues and environmental pollution stimulate research to find new health and hygiene related products with healing properties and minimum negative effect on the environment. Development of new, natural antibacterial agents has become one of the most important research areas to combat some pathogens such as Gram- positive and Gram-negative bacteria, fungi, algae, yeast, and some microorganisms which cause serious human infections. Lawsonia Inermis (henna) leaf extracts for preparation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 16 publications
1
37
0
1
Order By: Relevance
“…Napralert database, the world's largest natural product database currently documents 58850 plant species, from which 6550 plants exhibit significant antimicrobial activity and most of this plants possess extracts that can be used to treat infectious diseases. 63 Avci et al 64 reported the use of Lawsonia inermis (henna) as antimicrobial for the production of PEO and PVA nanofibers with bacteriostatic effect against Staphylococcus aureus and E. coli. Antimicrobial peptides are a wide family of small proteins with a broad spectrum of antimicrobial activity against bacteria, fungi, and viruses.…”
Section: Antimicrobial Materialsmentioning
confidence: 99%
“…Napralert database, the world's largest natural product database currently documents 58850 plant species, from which 6550 plants exhibit significant antimicrobial activity and most of this plants possess extracts that can be used to treat infectious diseases. 63 Avci et al 64 reported the use of Lawsonia inermis (henna) as antimicrobial for the production of PEO and PVA nanofibers with bacteriostatic effect against Staphylococcus aureus and E. coli. Antimicrobial peptides are a wide family of small proteins with a broad spectrum of antimicrobial activity against bacteria, fungi, and viruses.…”
Section: Antimicrobial Materialsmentioning
confidence: 99%
“…This unique chemical structure has led to the advantages of both properties of an elastomer and being processed as a thermoplastic material. The soft elastomeric part of SEBS shows high resistance to thermal degradation while the hard polystyrene section provides good thermoplastic performance as supported by the crystal formation . Additionally, the styrenic block copolymer has remarkable mechanical properties such as higher tensile strength with excellent elongation before break and elasticity, in addition to ease of deformation at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to chitosan [9], the most common antibacterial additives that are used in the modification of PVA's potential to inhibit the growth of microorganisms include silver nanoparticles [16], ZnO beads [10], plant extracts [24], nanocellulose [25], N-halamine [8], and poly(hexamethylene guanidine) (PHMG) [4]. PHMG is an antibacterial agent that is used in the range of antimicrobial polymeric materials [26,27].…”
Section: Introductionmentioning
confidence: 99%